Study of Fall Meteorites Over a Century (1922-2021) - Wagle, Bivu; Regmi, Kaustuv; Adhikari, Krishna Prasad (BMC Journal of Scientific Research, 2022)
Fall meteorites represents to those meteorites whose fall has been witnessed and are later collected from earth surface for further studies. Mass, number of fall events, types, type mass and mass trend of observed fall meteorites are analyzed over a period of recent century (1922-2021) in this paper. The total number of fall meteorites was found to be 706 with total mass of 42800 kg. Decade 2012-2021 and 1932-1941 had the highest number of recorded fall which was 94 times and 89 times respectively. Type L6 meteorite was found to have the greatest number of falls which is 151 times, followed by type H5 and L5 with 109 times and 55 times respectively. The meteorite of type, Iron III AB had the greatest meteorites mass of 23480 kg followed by H5 and L6 with mass 6615 kg and 2347.362 kg respectively. The massive meteorite fall of this century was of Iron III AB type (1947) which weighed 23 tones. The decade 1942-1951 had the highest fall meteorites mass of 24806kg and 1972-1981 had 4858 kg. Various regression model is fitted for the trend analysis of the mass. Over a period of this century, meteorites having mass greater than 100 kg has struck the earth for 32 times while mass greater than 1000 kg has struck for 6 times. The average time between two impacts of meteorite with mass greater than 100kg was calculated to be 3.12 years while mass greater than 1000 kg was found to be 16.6 years.